How monetary policy is made: Two Canadian tales - Pierre L. Siklos; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2013)
This paper examines the policy rate recommendations of the Bank of Canada's Governing Council (GC) and the C.D. Howe Institute's Monetary Policy Council (MPC) since 2003. We find, first, that differences in the median recommendations between the MPC and the GC are persistent but small (i.e., 25 bps). The median MPC recommendation is based on a higher steady state real interest rate. However, the response of the MPC and the GC to output and inflation shocks are, for the most part, comparable. Second, we are also able to examine the individual recommendations for the MPC. Estimates of the determinants of consensus inside the MPC or disagreement with the GC yield some useful insights. For example, disagreements are more likely when rates are proposed to rise than at other times. Equally interesting is the finding that the Bank of Canada conditional commitment on the overnight rate in 2009-10 has a relatively larger restricting impact on the MPC's median recommendation than the GC's target rate.
Keywords: E43; E52; E58; E61; E69; 330; Bank of Canada; central bank communication; committee behaviour; monetary policy committees; shadow councils; Taylor rules